Fostering a Natural Atmosphere; Improving Students’ Communication Skill in a Business Meeting - Lia Agustina; R. Setiawan (Universitas Pendidikan Mandalika, 2020)
Engaging a fun class creates a positive classroom atmosphere. Research has indicated that if a positive classroom atmosphere is created, students will have better learning and engage more, which means it is one of the most effective and powerful tools teachers can use to encourage students learning. Oral communication skill is essential for thinking and learning. By getting the knowledge of it, students would be able to express information, opinions, understand concepts, and would be able to discuss experience and expertise. The researcher used an Action Research Method. The purpose was to see the improvement of the students' ability to speak up. The subject was 32 students of Accountant Department – State Polytechnic of Malang. The result of the study showed that most students showed an improvement in all four language skills, but speaking skills had the most significant increase.